A missionary pioneer in the Far East;: a memorial of Divie Bethune McCartee ... - McCartee, Divie Bethune (Fleming H. Revell Company, 1922)
The man and his work: from an occidental viewpoint, by R.E. Speer.--The man as he regarded himself; Dr. McCartee's own story.--The man as an oriental Christian saw him, by Woh-Cong-eng.--The man as a fellow-worker knew him, by D. Murray.